"اثر استراتيجية (K.W.L) في تنمية التفكير الابداعي لدى طلاب الصف الخامس الادبي في مادة الجغرافية (Journal of the College of Basic Education, 2022)
The research aims to know the impact of the (KWL) strategy on developing creative thinking among students of the fifth literary grade in geography, the research was conducted in Baghdad, and the researcher identified the research community with all the fifth literary students in the General Directorate of Education for the second Rusafa, and the sample consisted of (60) students They were divided into two groups (experimental and controlling), and the two research groups were rewarded with (time age, pre-test for creative thinking), and after preparing the research requirements, the researcher adopted the research tool which is the measure of creative thinking, and after making sure the scale is correct and its stability and psychometric properties applied to the basic research sample, And Bast As long as the test Altaia (t-test) for two independent samples, the results showed superiority of the experimental group in creative thinking, all this researcher recommended some of the recommendations and suggested that some of the proposals